2021
DOI: 10.3390/nu13051404
|View full text |Cite
|
Sign up to set email alerts
|

Iodine Nutritional Status and Related Factors among Chinese School-Age Children in Three Different Areas: A Cross-Sectional Study

Abstract: We evaluated the iodine nutritional status and related factors among school-age children based on the 2016 National Nutrition and Health Surveillance of Children and Lactating Women; 3808 children from Hebei, Guangxi, and Zhejiang province were included in the study. Urinary iodine concentration (UIC), thyroid-stimulating hormone (TSH), body mass index (BMI), vitamin A (VA), and vitamin D (VD) were measured. The abnormal rate of UIC and TSH were assessed. Relationships between UIC/TSH and the possible factors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 17 publications
(17 reference statements)
2
10
0
Order By: Relevance
“…And iodine de ciency can accelerate lipolysis and fatty acid oxidation, and increase plasma TSH level without affecting thyroid hormone signal [30]. Our previous study on school-age children has also con rmed this phenomenon [9]. But obese mothers in this study showed higher MUIC, which was consistent with a Mexican study conducted in children from primary schools, nding a positive correlation between UIC values and BMI, and the prevalence of overweight and obesity [31].…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…And iodine de ciency can accelerate lipolysis and fatty acid oxidation, and increase plasma TSH level without affecting thyroid hormone signal [30]. Our previous study on school-age children has also con rmed this phenomenon [9]. But obese mothers in this study showed higher MUIC, which was consistent with a Mexican study conducted in children from primary schools, nding a positive correlation between UIC values and BMI, and the prevalence of overweight and obesity [31].…”
Section: Discussionsupporting
confidence: 90%
“…Since geographic in uences on the iodine status existed in pregnant and lactating women, neonates, and school-age children [26,27], and geographic locations with poor iodine status were suggested to identify [17], we then analyzed UIC differences among the three representative provinces. Our previous study concluded that the iodine nutritional status of school-age children varied among Hebei, Zhejiang and Guangxi, and lower MUIC and higher proportion of UIC < 100 µg/L was observed in Hebei and Zhejiang [9]. Similar to school children, the MUIC of mothers in Zhejiang was the lowest and the proportion of UIC < 100 µg/L in Zhejiang was the highest.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations